Efficient genome editing in filamentous fungi via an improved CRISPR‐Cas9 ribonucleoprotein method facilitated by chemical reagents. Issue 6 (25th August 2020) - Zou, Gen; Xiao, Meili; Chai, Shunxing; Zhu, Zhihua; Wang, Ying; Zhou, Zhihua
Summary: DNA double‐strand break (DSB) repair induced by the RNA‐programmed nuclease Cas9 has become a popular method for genome editing. Direct genome editing via Cas9‐CRISPR gRNA (guide RNA) ribonucleoprotein (RNP) complexes assembled in vitro has also been successful in some fungi. However, the efficiency of direct RNP transformation into fungal protoplasts is currently too low. Here, we report an optimized genome editing approach for filamentous fungi based on RNPs facilitated by adding chemical reagents. We increased the transformation efficiency of RNPs significantly by adding Triton X‐100 and prolonging the incubation time, and the editing efficiency reached 100% in Trichoderma reesei and Cordyceps militaris . The optimized RNP‐based method also achieved efficient (56.52%) homologous recombination integration with short homology arms (20 bp) and gene disruption (7.37%) that excludes any foreign DNA (selection marker) in T. reesei . In particular, after adding reagents related to mitosis and cell division, the further optimized protocol showed an increased ratio of edited homokaryotic transformants (from 0% to 40.0% for inositol and 71.43% for benomyl) from Aspergillus oryzae, which contains multinucleate spores and protoplasts. Furthermore, the multi‐target engineering efficiency of the optimized RNP transformation method was similar to those of methods based on in vivo expression of Cas9. This newly established genome editing system based on RNPs may be widely applicable to construction of genome‐edited fungi for the food and medical industries, and has good prospects for commercialization. Abstract : We report an optimized genome editing approach for filamentous fungi based on RNPs facilitated by adding chemical reagents. We increased the gene editing efficiency of RNPs significantly by adding Triton X‐100. Reagents related to mitosis and cell division furtherly increased ratio of edited homokaryotic transformants from filamentous fungus containing multinucleate spores and protoplasts.